Small Responsible Innovators and Open Innovation towards Sustainability: Networks Conditions - Marina Van Geenhuizen; Qing Ye (European Regional Science Association (ERSA), 2013)
Open innovation is key for innovators responding to major problems in the world, including energy, healthcare, water and the environment, and bringing transitions in socio-technical systems near. This paper has a focus on university spin-off companies as a channel of market introduction of new technology and responsible innovation. Although rich in technological knowledge, these companies suffer from lack of other resources, in particular, time, management experience and investment capital, reason why they need to limit their efforts in active participation in open innovation networks. The paper starts with a conceptual reflection on responsible innovation and open innovation practices in the frame of transitions towards higher sustainability levels. Responsible innovation can be seen as a transparent, interactive, process by which societal actors and innovators become mutually responsive to each other with a view to the (ethical) acceptability, sustainability and societal desirability of the innovation and its marketable products. Being engaged in responsible research and innovation means a relatively intense participation in the complex networks concerned. The empirical analysis draws on 105 university spin-off companies and demonstrates that almost 60% of the companies are engaged in responsible innovation, with medical care/cure, sustainable energy, sustainable mobility, and waste treatment/recycling as the largest sectors, and that a good 40% are not involved in responsible innovation. Derived from regression analysis, the results indicate that responsible innovation is one of the drivers of open innovation in terms of size of the knowledge pool (themes) and diversity of this pool (different partners). However, diversity in the knowledge pool tends to influence growth of the companies negatively. Accordingly, it seems that the limited resources of university spin-off companies require ?selectivity" in choosing partners as a key condition for participation in networks (platforms) aimed at socio-technical systems" change. This means to connect with merely one large companies as a launching customer and with a prominent investor, each on their turn being connected with a large diversity of network partners. At the same time, the need for selectivity tends to bring university spin-off companies in peripheral regions in a disadvantageous position compared to their counterparts in metropolitan areas, given the need for frequent interaction and a small chance to find the best matching partner(s) within the region. The paper concludes with implications of the findings and future research avenues
Keywords: 330; responsible innovation; open innovation networks; university spin-off companies; selectivity; socio-technical systems; transitions